A comprehensive study on experimental analysis and development methods of chicken feather fiber reinforced bio composites. (2021) - Bansal, Gagan; Jain, Yash; Ahmed, Yusuf; Kishore, Chandra; Agarwal, Vartika
Abstract: The current review article deals with the study of Chicken Feather Fiber based Bio Composite materials. Combination of a reinforcing material and a Matrix is known as composite material. Biocomposite materials developed from the livestock waste are the future of sustainable material technology. Here, in the current study, an effort is made to highlight the work of several researchers working in the field of development and characterization of Chicken Feather Fiber (CFF) reinforced biocomposite materials. Also the effect of shape, size and orientation of CFF as reinforcing fiber in various nonmetallic matrices is elaborately discussed. Various mechanical properties like tensile strength, compressive strength, flexural strength, hardness, material bonding, water absorption and thickness swelling, insulation characteristics and impact strength of various prepared CFF filled composite samples are compared based on specific applications. Review on Characterization of Reinforcement of Chicken Feather fiber with several matrix materials like Epoxy Resin (CY-230), jute, team wood, polypropylene, MESCO, etc is discussed. Also the application of using CFF as a reinforcing material is elaborated. Finally, the gap analysis is discussed in order to enhance the research in the field of material development and to optimize the existing methodology, characteristics and applications off CFF reinforced biocomposite materials. The major future prospective of the analysis is to develop an idea for cost effective, sustainable, light weight, high strength and high power materials from composite materials by use of waste materials abundantly available.